Analysis of short-term total hospital costs and current primary cost drivers of coiling versus clipping for unruptured intracranial aneurysms. (2nd June 2014) - Duan, Yifei; Blackham, Kristine; Nelson, Jeff; Selman, Warren; Bambakidis, Nicholas
Abstract : Background: No randomized controlled trial has successfully compared outcomes between endovascular coiling and microsurgical clipping for unruptured intracranial aneurysms (UIAs). Objective: To perform a cost comparison between index hospitalizations of patients with UIAs treated with coil embolization or surgical clipping to identify the current primary drivers of costs of either management approach. Methods: We obtained index hospitalization costs for 125 cases of UIAs treated with coiling or clipping from 2010 to 2012 at our institution. Comparisons were stratified based on patient age, gender, aneurysm size, and aneurysm location. Using linear regressions, we identified clinical parameters that drive total hospital costs. Results: 69 cases were treated with clipping and 56 cases were treated with coiling. Morbidity and length of stay for patients treated with clipping was higher. Total hospital costs and variable direct costs for clipping were significantly lower than for coiling (p=0.003, p<0.001, respectively). Fixed direct costs and fixed indirect costs for clipping were higher than for coiling (p<0.001, p<0.001, respectively). Variable direct costs comprised 50.5% and 68.6% of total hospital costs for clipping and coiling, respectively (p<0.001). Length of stay, aneurysm size, and patient age drove total hospital costs for clipping. Length of stay was a weak driver of total hospital costs for coiling. Conclusions: Total index hospitalization costs for clipping are lower than for coiling. Costs of clipping and coiling are driven by different clinical variables. The cost of coils and devices is the predominant contributor to the higher total costs of coiling.